2011
DOI: 10.1103/physrevlett.107.062503
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Particle Radioactivity of Superheavy Nuclei

Abstract: The concept of heavy-particle radioactivity (HPR) is changed to allow emitted particles with Z(e) > 28 from parents with Z > 110 and daughter around (208)Pb. Calculations for superheavy (SH) nuclei with Z = 104-124 are showing a trend toward shorter half-lives and larger branching ratio relative to α decay for heavier SHs. It is possible to find regions in which HPR is stronger than alpha decay. The new mass table AME11 and the theoretical KTUY05 and FRDM95 masses are used to determine the released energy. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
144
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(148 citation statements)
references
References 25 publications
3
144
1
Order By: Relevance
“…In view of the excellent agreement [9,10] of PCM with the available [11,12] experimental data on cluster decays of heavy parent nuclei with Z=87 to 96, here in this work, half lives of isotopes of SHE element Z=115 have been predicted and compared with the existing [4,5] theoretical results to test the extent of validity of this formalism. Since the fragmentation process depends on the collective clusterization approach, in PCM, not only the shapes of parent, daughter and cluster are important but also of all other possible fragments anticipated in the decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the excellent agreement [9,10] of PCM with the available [11,12] experimental data on cluster decays of heavy parent nuclei with Z=87 to 96, here in this work, half lives of isotopes of SHE element Z=115 have been predicted and compared with the existing [4,5] theoretical results to test the extent of validity of this formalism. Since the fragmentation process depends on the collective clusterization approach, in PCM, not only the shapes of parent, daughter and cluster are important but also of all other possible fragments anticipated in the decay.…”
Section: Introductionmentioning
confidence: 99%
“…Besides beta decay, only α-decay and spontaneous ¿ssion of SHE nuclei have been experimentally observed up to now. Knowing that the role of shell effects is the central feature in the cluster decay process studied so far, the domain of cluster radioactivity has been further widened by Poenaru et al [4,5]. They explored the heavy-particle radioactivity of superheavy nuclei on the basis of Analytical Super Asymmetric Fission Model (ASAFM) in which unstable parent nuclei having Z >110 decays into a cluster with Z cluster >28 and a doubly magic daughter around 208 Pb.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical calculations related to cluster decays in terms of quantum tunneling can be performed by fission-like or alpha-like theory. Numerous papers in which authors have used different methods have been published on finding half-lives of these cluster emissions with and without deformation [30][31][32][33][34][35][36][37][38]. More recently, intensive works have been continuing in order to get closed analytical formulas like the Geiger and Nuttall rule for the cluster decays of isotopes [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that for superheavy nuclei with atomic numbers Z > 121 [29,43] αD may be stronger than CD or spontaneous fission.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the analytical and numerical superasymmetric fission (ASAF [23] and NUSAF) models were used together with fragmentation theory developed by the Frankfurt School, and with penetrability calculations like for α decay, to predict cluster (or heavy particle) radioactivity [24][25][26][27][28][29]. The extended calculations [30][31][32] have been used to guide the experiments and as a reference for many theoretical developments.…”
Section: Introductionmentioning
confidence: 99%